Social Security Organization (SOCSO): the effectiveness of studying Employee Performance Appraisal System (EPAS) / Ummi Hanisah Jusoh - Jusoh, Ummi Hanisah (2009)
The effectiveness of studying Employee Performance Appraisal System (EPAS) in Social Security Organization (SOCSO) requires people with high determination to play their roles by providing a good performance in the organizations and for their own selves. Besides that, EPAS also help in building the quality employees and increase the performance level to the excellent level to achieve the goals. This determination has to be developing in SOCSO where the employees have to prepare mentally and physically during in their real job environment. Through this study, hopefully it will enhance the productivity and increase the competency on job performance. This paper will help to measure the problems that occurred in Social Security Organization (SOCSO) especially employees’ problems. By using the EPAS, SOCSO will achieve their vision is to become an ideal and excellent social security leader in Malaysia.